Wrongfulness of a court’s decisions, acts and/or omissions as a condition of tortious obligations in Ukraine - Kulitska, Sofia V. (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2016)
An attempt to analyze one of the necessary conditions determining the obligations to compensate for damage caused by the judiciary is made in the article. The author focuses on the wrongfulness of a court’s decisions, acts and/or omissions as a condition of such obligations. It is emphasized that the category “miscarriage of justice” is used as a generic term for the aforementioned forms of wrongful behavior under the provisions of some international instruments and the legislation of some foreign countries. Meanwhile, the author shows that the incorporation of such an approach into national legislation is inappropriate. It is concluded that the problem of extending the list of wrongful actions of judicial bodies and their officials is particularly relevant for Ukraine, considering the practice of the ECHR. Special attention is given to the case of compensation for damage caused to an individual or legal entity as a result of a court rendering an illegal decision in a civil case.